Comparing the Effects of Group Training of Mindful Parenting Skills and Psychological Capital on Stress and Psychological Flexibility in Mothers with Blind Girl Students - Fatemeh Sharif Mohammadi; Maryam Chorami; Tayebeh Sharifi; Ahmad Ghazanfari (Shiraz University of Medical Sciences, 2020)
Background: Mothers with a blind child are more involved with the child's behavioral problems and experience higher levels of stress and psychological crisis. The present study aimed to investigate the effects of mindful parenting skills and psychological capital on stress and psychological flexibility in mothers with blind girls. Methods: The research method was quasi-experimental with a pre-test, post-test, and follow-up design and a control group. The sample consisted of 72 mothers with blind girl students selected by convenience sampling. We randomly divided the participants into two experimental groups (training of mindful parenting skills and psychological capital training) and a control group (n=24 per group). The research instrument included the Parental Stress Inventory and the Acceptance and Action Questionnaire. Results: The training intervention sessions decreased the stress levels and promoted the psychological flexibility of mothers with blind girl students in the experimental groups, compared to the control group (P=0.001). The mean±SD of the post-test scores of stress and psychological flexibility was (90.37±5.10) and (63.00±3.78) in the mindful parenting group and (104.87±4.57) and (52.37±3.32) in the psychological capital group, which was significantly different from the control groups. The group training of mindful parenting skills, in comparison to psychological capital, was more effective in reducing stress and increasing psychological flexibility among the mothers. Conclusions: The group training of mindful parenting skills using mindfulness techniques was more effective in reducing stress and increasing the psychological flexibility.